Physiological Repairing of Postpartum Rat Uterus Treated with Pelawan (Tristaniopsis obovata Benn.) Extract - Yusfiati; W. Manalu; H. Maheshwari; Andryanto (Faculty of Animal Science, Bogor Agricultural University, 2021)
The study examined the effectiveness of ethyl-acetate fraction of Pelawan extract on the activities of superoxide dismutases in physiological repairing of uterus in postpartum rat based on SOD activity, MDA concentration, and Cu, Zn SOD expressions. The experiment was arranged with a factorial, completely randomized design. Seventy-two female rats were divided into 4 groups, namely, control 1 (P01= 9), control 2 (P02= 9), giving birth once (P1= 27), and giving birth twice (P2= 27). The experimental rats were given treatments orally with 4 doses, namely 0 mg/kg BW, 50 mg/kg BW, 100 mg/kg BW, and 150 mg/kg BW. Observation data were taken on days 0, 3, and 5 after parturition. Variables measured were SOD activity, MDA levels, and the number of cells in the uterine tissue expressing Cu, Zn SOD. The results of studies on the condition of P01, P02, P1, and P2 showed significant changes in Cu, Zn SOD expressions. The low of SOD and MDA activities were found at doses of 100 mg and 150 mg. The high number of cells expressing Cu, Zn SOD in the epithelium cells and gland cells were found at a dose of 100 mg. Antioxidant plant extracts and their dosages determine the activities of SOD, MDA, and Cu, Zn SOD expressions in the uterus that will affect the process of repairing and involution of uterine tissue. Allegedly, the bioactive compounds extracted at certain doses effectively affect the physiological repair of cells in the uterine tissue of postpartum mothers.